Discrete-time predictive trajectory tracking control for nonholonomic mobile robots with obstacle avoidance. (25th September 2019) - Zhang, Jingjun; Zhang, Shaobo; Gao, Ruizhen
This article presents a tracking control approach with obstacle avoidance for a mobile robot. The control law is composed of two parts. The first is a discrete-time model predictive method-based trajectory tracking control law that is derived using an optimal quadratic algorithm. The second part is the obstacle avoidance strategies that switch according to two different designed obstacle avoidance regions. The controllability of the avoidance control law is analyzed. The simulation results validate the effectiveness of the proposed control law considering both trajectory tracking and obstacle avoidance.